Impact of educational videos and user guide on indwelling pleural catheter caregiver training and unplanned healthcare encounters - Si Ling Young; Brian Lee Wei Chua; Qiao Li Tan; Carrie Kah-Lai Leong; Ivana Gilcrist Chiew Sian Phua; Jane Jing Yi Wong; Wen Ting Lim; Kendra Jing Ying Tang; Aaron Jun Jie Tan; Fena Ming Qin Lee; Ken Junyang Goh (BMJ Open Quality)
Background Indwelling pleural catheters (IPCs) are an effective first line option for the management of symptomatic malignant pleural effusions. However, patients with IPCs often require unplanned healthcare encounters (UHEs) due to complications or concerns with IPC care and drainage.Local problem There is a lack of readily accessible IPC-specific educational material to support caregiver training (CGT). As IPC care and drainage are performed primarily by patients and caregivers in our country due to the lack of community nursing support, ineffective CGT may lead to increased UHEs due to caregiver knowledge gaps or poor confidence in managing and caring for IPCs.Aims We aim to reduce the number of IPC-related UHEs.Methods and interventions We used a 5-why diagram and identified a lack of appropriate educational material as a key factor contributing to repeated UHEs. We therefore produced and employed IPC-specific educational videos and user guides, using a ‘Plan-Do-Study-Act’ approach, into our CGT programme. Patient demographics and clinical outcomes were collected prospectively for 166 consecutive patients with IPC insertions, with 72 patients in the preintervention group and 94 in the postintervention group. Survey questionnaires addressing caregiver competency and confidence were also administered after CGT using these tools.Results There was a significant decrease in the proportion of patients who had ≥2 (8.5% vs 40.9%, p<0.001) or ≥3 UHEs (3.2% vs 31.8%, p<0.001) in the intervention group. There was also a higher caregiver competency score achieved in the intervention group (7 (IQR: 7–7) vs 5 (IQR: 5–7), p<0.001). There was no difference in overall complication and IPC-related infection rates between groups.Conclusion IPC-specific educational videos and resources, which are readily accessible and easily implemented into CGT programmes, reduce UHEs due to IPC-related issues and may improve caregiver knowledge and competency in IPC care and drainage.